Research, design and fabrication dynamic balancing machine using flexible bearings - Tran , Thanh Lam (Journal of Technical Education Science, 2016)
Dynamic balancing machine is one of the important test devices to determine the location and amount of unbalance of rotor. Machines are often designed basing on the principle of using hard bearings for force measurement sensors or flexible bearings for oscillation sensors. Currently, the machines are imported machines or offered from a few domestic enterprises with very high costs. To meet the needs of research and training as well as to gradually master the technology on a large scale, a dynamic balancing machine using flexible bearings which can determine the amount of unbalance for rotor <15 kg, has been manufactured. The measured vibration signal by the sensor mounted on the bearings are collected and stored in the microcontroller dsPIC30F4011, then processed computer to provides calculation for corresponding information. Test results show that the dynamic newly manufactured balancing machines using flexible bearings accuracy about G6.3 (ISO 1940).